Penentuan Strategi Bersaing Terbaik pada E-Commerce Menggunakan Metode AHP dan Game Theory - Aulia Medangara Hakim; Yudi Mahatma; Widyanti Rahayu (JMT (Jurnal Matematika dan Terapan), 2024)
Based on the iPrice.co.id website, there are five e-commerce sites in Indonesia with the highest number of visitors. This is caused by the competitive strategy implemented by each e-commerce in order to win or maintain competition with consideration of the most attractive strategy for potential customers. The purpose of this study is to determine the best competitive strategy that needs to be implemented by e-commerce using game theory and consumer evaluation of e-commerce and supporting variables using the AHP (Analytical Hierarchy Process) method. The sample of this research is Jakarta citizens who are e-commerce users. The results of the research on the AHP method obtained e-commerce ranking results with the highest priority ranking to the lowest, namely Tokopedia, Shopee, Lazada, Blibli and Bukalapak. The variables that consumers pay attention to when making purchases on e-commerce from the highest priority to the lowest, namely Security, Trust, Free Shipping, Lots of Promos, Price, Product Quality, Payment Methods, Web Appearance, Product Brands and Product Diversity, where the 6 variables with the highest priority are then selected and these variables are used to determine the best competitive strategy using the game theory method. The results from game theory show that for Tokopedia e-commerce it is necessary to use a Product Quality strategy, Flood of Promos, and Trust, for Shopee namely Free Shipping, Lots of Promos and Security, for Lazada namely Product Quality, Free Shipping, Lots of Promos, and Security, for Bukalapak namely Product Quality, Price, Free Shipping, Lots of Promos, Trust, and Security, for Blibli namely Price, Free Shipping, Lots of Promos and Security.